SURVEY LEVEL OF UNDERSTANDING OF PHYSICAL ACTIVITY AND PHYSICAL ACTIVITY LEVEL AND ANTHROPOMETRIC STATUS - Arika Umi Zar in; Imam Sugeng; Roudhotul janah (Gladi : Jurnal Ilmu Keolahragaan, 2024)
Students of Physical Education Health and Recreation Faculty of teacher training and education are prepared to become competent educators in the field of sports. One of the skills competencies required is understanding and skills in measuring physical activity levels, understanding physical activity and anthropometry.  The purpose of this study was adalah to determine and understand the measurement aktivitas of physical activity, understanding of physical activity and anthropometric status of students of Physical Education Health and Recreation FKIP. This study is cross-sectional research on students who administer the test and measurement of sports. Understanding of the level of physical activity measured by metode the test method, the level of physical activity was measured using a questionnaire GPAQ (global Physical Activity Questionanire) and tipe body type or somatotype was measured based on the health Charter Manual. Then the data is processed in a descriptive and correlation Person to determine the relationship between the level of understanding of physical activity, physical activity level and anthropometry using SPSS. The results showed that in all students who manage the course of sports tests and measurements have level a good level of physical activity baik GPAQ score an average of 7248.13 ° 2420.5 METs. Correlation test showed positive correlation between the level of understanding of physical activity and physical activity level correlation p < 0.05.